No on Prop 6 Fundraiser in Watkins Family Backyard - Watkins, Howard::::::::: (1978)
William Leifer holding Gregory Leifer, ?, Ed Asner, June Loring, Cantor Michael Loring, David Smith Chris Petersen (white shirt) in background